La ficcionalización del erotismo en los cuentos de Germán Espinosa - Orlando Araújo Fontalvo (Caravelle)
Eroticism is one of the most significant subject matters in short-story teller Germán Espinosa’s work. In order to understand the nature of this recurrence it is necessary to revise carefully the short fictions in which eroticism manifests itself as an unassailable force, through an impulse knowing no rest nor respite, revealing an anomic society at its deepest and darkest.